2009
DOI: 10.1149/1.3196244
|View full text |Cite
|
Sign up to set email alerts
|

Operating Behavior and Scale-Up of an ECPrOx Unit for CO Removal from Reformate for PEM Fuel Cell Application

Abstract: Recently, an approach involving electrochemical preferential oxidation (ECPrOx) of CO was suggested as having the potential to replace the PrOx concept for deep CO removal from reformate gas in proton exchange membrane (PEM) fuel cells. The first part of this paper deals with the characterization of such an ECPrOx unit from a reaction engineering point of view. Based on a spatially lumped, isothermal model, the qualitative selectivity-conversion behavior is discussed for varying feed flow rates and CO inlet mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…Such a configuration allows independent potential oscillations in each cell. This in turn enables deeper CO removal than two cells connected in parallel, as illustrated in Figure 24 213. In a parallel connection, the upstream cell is unable to oscillate independently and CO conversion is hindered because it is enslaved by its downstream counterpart.…”
Section: Dynamic Electro‐oxidation Of Carboncontaining Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a configuration allows independent potential oscillations in each cell. This in turn enables deeper CO removal than two cells connected in parallel, as illustrated in Figure 24 213. In a parallel connection, the upstream cell is unable to oscillate independently and CO conversion is hindered because it is enslaved by its downstream counterpart.…”
Section: Dynamic Electro‐oxidation Of Carboncontaining Fuelsmentioning
confidence: 99%
“… Time evolution of selected variables: a) anode overvoltage and b) CO outlet mole fraction for the electrical series connection of two ECPrOx reactors; c) anode overvoltage and d) CO outlet mole fraction for electrical parallel connection. Reproduced from reference 213 with permission from the Electrochemical Society. …”
Section: Dynamic Electro‐oxidation Of Carboncontaining Fuelsmentioning
confidence: 99%
“…Besides the cited data of half-cell experiments, there are also several recent papers on the kinetic instabilities in low temperature proton exchange membrane fuel cells ͑PEMFCs͒ fed with H 2 /CO mixtures. [28][29][30][31][32][33][34][35] In most cases, oscillatory kinetics are observed in PEMFCs with a Pt/C cathode fed with oxygen and a PtRu/C anode fed with a H 2 /CO mixture. Besides the fundamental aspects that underlie this complex system, considerably higher average power densities are observed under an oscillatory regime when compared with those observed under a stable steady state.…”
mentioning
confidence: 99%
“…105 Hanke-Rauschenbach (2009) studied the oscillatory behaviour of potential using the model presented by as a base, and compared the behaviour of two ECPrOx reactors with electrical connections in series and in parallel. 42,142 It was concluded that the CO conversion is improved in the series system due to the independent oscillations of each unit. The units connected in parallel oscillate simultaneously, affecting the performance of the system.…”
Section: Electrochemical Preferential Oxidation (Ecprox)mentioning
confidence: 99%